Racial differences in dietary antioxidant intake and cardiac event-free survival in patients with heart failure. (April 2018) - Wu, Jia-Rong; Song, Eun Kyeung; Moser, Debra K; Lennie, Terry A
Background: Heart failure is a chronic, burdensome condition with higher re-hospitalization rates in African Americans than Whites. Higher dietary antioxidant intake is associated with lower oxidative stress and improved endothelial function. Lower dietary antioxidant intake in African Americans may play a role in the re-hospitalization disparity between African American and White patients with heart failure. Objective: The objective of this study was to examine the associations among race, dietary antioxidant intake, and cardiac event-free survival in patients with heart failure. Methods: In a secondary analysis of 247 patients with heart failure who completed a four-day food diary, intake of alpha-carotene, beta-carotene, beta-cryptoxanthin, lutein, zeaxanthin, lycopene, vitamins C and E, zinc, and selenium were assessed. Antioxidant deficiency was defined as intake below the estimated average requirement for antioxidants with an established estimated average requirement, or lower than the sample median for antioxidants without an established estimated average requirement. Patients were followed for a median of one year to determine time to first cardiac event (hospitalization or death). Survival analysis was used for data analysis. Results: African American patients had more dietary antioxidant deficiencies and a shorter cardiac event-free survival compared with Whites ( p = .007 and p = .028, respectively). In Cox regression, race and antioxidant deficiency were associated with cardiac event-free survival before and after adjusting for covariates. Conclusion: African Americans with heart failure had more dietary antioxidant deficiencies and shorter cardiac event-free survival than Whites. This suggests that encouraging African American patients with heart failure to consume an antioxidant-rich diet may be beneficial in lengthening cardiac event-free survival.